2007
DOI: 10.1002/jcu.20292
|View full text |Cite
|
Sign up to set email alerts
|

Alagille syndrome: Prenatal sonographic findings

Abstract: We report a case of Alagille syndrome in which sonographic examination revealed the presence of angulation of the fetal spine due to vertebral fusion as well as tetralogy of Fallot. Histologic examination after pregnancy termination revealed the presence of agenesis of the gallbladder with a paucity of intrahepatic bile ducts, leading to the diagnosis of Alagille syndrome. In the presence of cardiac and axial skeletal anomalies, attention should be paid to the fetal gallbladder, whose absence would signal a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the timing of the development of the liver abnormality is not fully understood. Previously, an aborted fetus with ALGS was found to have paucity of intrahepatic bile duct at gestational age 22 weeks [Alessandro et al, ], but the mouse model of ALGS due to Jag1 and Notch2 double knock out revealed the absence of liver pathology during embryogenesis [Lozier et al, ]. Hence, liver pathology associated with ALGS probably emerges during the second trimester, when the discordance between twins was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the timing of the development of the liver abnormality is not fully understood. Previously, an aborted fetus with ALGS was found to have paucity of intrahepatic bile duct at gestational age 22 weeks [Alessandro et al, ], but the mouse model of ALGS due to Jag1 and Notch2 double knock out revealed the absence of liver pathology during embryogenesis [Lozier et al, ]. Hence, liver pathology associated with ALGS probably emerges during the second trimester, when the discordance between twins was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly reported prenatal features of ALGS from eight case reports include IUGR in 75% of cases, cardiac anomalies (three cases, TOF in two and severe pulmonary stenosis in one), and hemivertebrae and two-vessel cord in two cases [ 78 81 , 88 , 89 ]. Other reported features include severe lumbosacral kyphoscoliosis, absent gallbladder, prominent chin, and prominent stomach with ascites [ 80 , 90 ]. Fetuses suspected of having ALGS should receive detailed cardiac imaging (fetal echocardiography or MRI).…”
Section: Alagille Syndrome and Pregnancymentioning
confidence: 99%
“…A few case reports have documented the prenatal findings in ALGS using a detailed ultrasound scan, including fetal hemi vertebrae in the lower thoracic region, cardiac changes, and absent gallbladder, in a fetus with JAG1 mutation 10 ( Figure 1A–C ).…”
Section: Systemic Manifestations and Clinical Descriptionmentioning
confidence: 99%